ABC The alphabet from the sky - Groß, Benedikt 1980- (Price Stern Sloan, An Imprint of Penguin Random House, 2016)
Discover the alphabet from a bird's-eye view! Geographer and designer duo Benedikt Gross and Joey Lee have taken the alphabet to new heights-literally! Using satellite imagery and computer technology, the pair has discovered "accidental letters" all over the world: in roads, rivers, buildings, lakes, and more. Take a journey around the Earth in 26 letters with this special book